Exercise oscillatory ventilation in patients with advanced heart failure with and without left ventricular assist device. Issue 1 (21st September 2022) - Wernhart, Simon; Papathanasiou, Maria; Jakstaite, Aiste; Hoffmann, Julia; Schmack, Bastian; Hedderich, Jürgen; Ruhparwar, Arjang; Rassaf, Tienush; Luedike, Peter
Abstract: Background: Exercise oscillatory ventilation (EOV), indicating pathological fluctuations on pulmonary arterial pressure, is associated with mortality in patients with heart failure (HF). Whether left ventricular assist device (LVAD)‐induced ventricular unloading can reverse EOV and may prevent short‐term rehospitalization has not been investigated. Methods: We performed a retrospective single‐center in‐ and outpatient analysis of patients with ( n = 20, LVAD) and without ( n = 27, HF) circulatory support and reduced ejection fraction (EF, 22.8 ± 7.9%). The association of cardiopulmonary exercise testing (CPET) variables and 3 months‐rehospitalization (3MR) as a primary outcome was analyzed. Furthermore, CPET variables were compared regarding the presence of EOV (+/−). Results: Lower VO2peak (11.6 ± 4.9 ml/kg/min vs. 14.4 ± 4.3 ml/kg/min, p = 0.039), lower increase of PETCO2 (CI = 0.049–1.127; p = 0.068), and higher VE/VCO2 (43.8 ± 9.5 vs. 38.3 ± 10.6; p = 0.069) were associated with 3MR. Flattening of O2 pulse (CI = 0.139–2.379; p = 0.487) had no impact on 3MR. EOV was present in 59.5% ( n = 28/47) of patients, without a significant difference between LVAD and HF patients ( p = 0.959). Patients with HF/EOV+ demonstrated significantly lower VO2peak compared with HF/EOV− ( p = 0.039). LVAD/EOV+ displayed significantly lower EF ( p = 0.004) and fewer aortic valve opening than LVAD/EOV− ( p = 0.027). Conclusions: Lower VO2peak, but not EOV, was associated with 3MR. EOV occurred at a similar rate in LVAD and HF patients, which may illustrate insufficient unloading during exercise in chronic LVAD therapy and may contribute to the limited exercise capacity following LVAD implantation. Simultaneous CPET and right heart catheterization studies are needed to elucidate whether EOV may serve as a non‐invasive predictor of insufficient LV unloading necessitating LVAD reprograming. Abstract : Peak oxygen consumption, VO2peak, was associated with short‐term 3‐months‐rehospitalization in heart failure patients with reduced ejection fraction (HFrEF). Exercise oscillatory ventilation (EOV), representing fluctuations of pulmonary artery pressure, can be observed in heart failure patients with reduced ejection fraction with and without left ventricular assist device (LVAD). VO2peak was significantly lower in HFrEF patients with EOV and without circulatory support, while VO2peak was equally low on LVAD support with and without EOV.